Fair Budgeting Formulation for O&M of Irrigation Using Multi-Criteria Decision Analysis: WA and AHP Methods - Soentoro, Edy Anto; Rohmat, Faizal I.W.; Vurnamawati, Vitta (Jurnal Teknik Sipil, 2014)
Abstract. Operation and Maintenance (O&M) budget provided by the Government of Indonesia for irrigation, so far, is based on the size of irrigated area only. Meanwhile, the actual O&M costs of an irrigation area also depend on the topographic terrain, canal density/length, irrigation structure density, and infrastructure damages that influence to the proper function of irrigation system. Thus, the O&M budget does not represent the actual cost needed. The purpose of this study is to find method for fair budgeting O&M irrigations based on Multi-Criteria Decision Analysis (MCDA): Weighted Average (WA) and Analytic Hierarchy Process (AHP) methods. As case study, the methods are applied on nine irrigation areas with various topographical conditions. The results are then compared with the conventional O&M budget. Four criteria are used to assess the irrigation areas above: canal density/length (m/ha), structure density (per hectare), infrastructure damages (%), and size of the irrigation area. The result shows that O&M budgeting using WA and AHP methods gives more fairness and closer to the actual budget needed, compared with the government budgeting that based on the size of irrigation area only. While in general, result using AHP method tends to be more sensitive than that using WA method. Abstrak. Anggaran untuk Operasi dan Pemeliharaan (O&P) daerah irigasi dari pemerintah Indonesia, saat ini, hanya berdasarkan pada luas daerah irigasi saja. Pada kenyataannya, biaya O&P dari suatu daerah irigasi juga tergantung pada kondisi topografi, panjang/kerapatan saluran, kepadatan bangunan irigasi, dan kerusakan infrastruktur yang berpengaruh terhadap berfungsinya system irigasi dengan benar. Jadi, anggaran O&P pada saat ini tidak mewakili biaya yang sebenarnya dibutuhkan. Tujuan dari penelitian ini adalah mencari cara yang lebih tepat dalam menentukan penganggaran O&P daerah irigasi berdasarkan Multi-Criteria Decision Analysis (MCDA): metoda Weighted Average (WA) dan Analytic Hierarchy Process (AHP). Sebagai studi kasus, kedua metoda tersebut diterapkan pada 9 daerah irigasi dengan berbagai kondisi topografi. Hasilnya kemudian dibandingkan dengan anggaran O&P yang ada. Empat kriteria digunakan dalam menilai 9 daerah irigasi tersebut, yaitu: panjang/ kerapatan saluran (m/ha), kepadatan bangunan air (per ha), kerusakan infrastruktur (%),dan luas daerah irigasi. Hasil penelitian menunjukkan bahwa menentukan anggaran O&P dengan metoda WA dan AHP memberikan hasil yang lebih adil dan lebih dekat dengan biaya yang dibutuhkan, dibandingkan dengan anggaran saat ini yang hanya berdasarkan pada luas daerah irigasi saja. Secara umum, hasil menggunakan metode AHP cenderung lebih sensitif dibandingkan dengan metode WA.